Dissent and authority in early modern Ireland - Wong, Jane Yeang Chui (Routledge, Taylor & Francis Group, 2020)
King Johan (1538), King John, and the Henrician reformation – Englishness and loyalty in Gerald of Wales' Expugnatio Hibernica (1189) and Holinshed's Irish chronicle – Portrait of a lord deputy : Sir Henry Sidney in Ireland and on the page – Negotiating violence and equity in Edmund Spenser's
9780367257750
Keywords: English literature; Irish in literature; Nationalism and literature